MODEL PEMBERDAYAAN MASYARAKAT DAN STRATEGI PEMASARAN PADA PENGEMBANGAN DESA WISATA RUMAH BUDAYA WATULIMO YANG BERBASIS INDUSTRI KREATIF DI KABUPATEN TRENGGALEK - Pesta Asni W. Napitulu; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Most of the tourism villages in Rumah Budaya Watulimo and Regencies only present the potential for local beauty of their respective regions, but have not yet touched on the development of creative industries by utilizing the existing potentials in those areas. The development of a tourism village generally has a positive impact on the life of the village community, especially the physical environment, economic, social and cultural conditions of the community around the tourist area. However, the addition of creative industries will be able to have a more positive impact on the people's economy. This study aims to implement community empowerment, especially for women and children as educational media in developing creative industry-based tourism villages in Trenggalek and districts. This research includes action research. The community empowerment strategy refers to the Asset Based Community Development (ABCD) methodology or Asset-Based Community Assistance. In terms of implementation. The collected research data is then processed and analyzed descriptively. The results showed that the implementation of community empowerment was carried out through the fashion creative industry in the tourist village and training in the corncob craft creative industry. The involvement of women in the corncob creative industry training is given starting from the processing of raw materials to a variety of products, as well as training in packing models and marketing programs, so that they are not only able to produce but also able to do marketing. In terms of involving children, this training is provided in the form of providing education on knowledge and skills ranging from processing raw materials to various products, besides that children are also taught about the creativity of the exhibition or display of products from the handicraft.